Iqbal Humanism and Human Rights - Mustofa Anshori Lidinillah; Mukhtasar Syamsuddin; Arqom Kuswanjono (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2023)
Contrasting religion with human rights is a critical response that is unproductive because basically the relationship between religion and human rights is ambivalent. Meanwhile, freedom of religion is understood as part of human rights, but in reality, religious practices emerge which result in violations of human rights. This research wants to answer the question of how to bridge the relationship between religion and human rights by taking the case of Iqbal's concept of humanism,